2017
DOI: 10.1002/cam4.1146
|View full text |Cite
|
Sign up to set email alerts
|

Digital PCR analysis of circulating tumor DNA: a biomarker for chondrosarcoma diagnosis, prognostication, and residual disease detection

Abstract: Conventional chondrosarcoma is the most common primary bone tumor in adults. Prognosis corresponds with tumor grade but remains variable, especially for individuals with grade (G) II disease. There are currently no biomarkers available for monitoring or prognostication of chondrosarcoma. Circulating tumor DNA (ctDNA) has recently emerged as a promising biomarker for a broad range of tumor types. To date, little has been done to study the presence of ctDNA and its potential utility in the management of sarcomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 30 publications
(40 reference statements)
2
25
0
Order By: Relevance
“…The cfDNA fraction released from tumor tissues, called circulating tumor DNA (ctDNA), may reflect the genetic aberrations of cancer cells at a given time. cfDNA was recently detected in plasma of bone sarcoma (Gutteridge et al , 2017; Shukla et al , 2017; Barris et al , 2018) and STS patients (Boonstra et al , 2018; Eastley et al , 2018; Namløs et al , 2018; Ogino et al , 2018; Shulman et al , 2018). In these studies, total cfDNA levels were frequently increased in the plasma of sarcoma patients compared with the cancer‐free controls.…”
Section: Epidemiology Of Sarcomamentioning
confidence: 99%
See 1 more Smart Citation
“…The cfDNA fraction released from tumor tissues, called circulating tumor DNA (ctDNA), may reflect the genetic aberrations of cancer cells at a given time. cfDNA was recently detected in plasma of bone sarcoma (Gutteridge et al , 2017; Shukla et al , 2017; Barris et al , 2018) and STS patients (Boonstra et al , 2018; Eastley et al , 2018; Namløs et al , 2018; Ogino et al , 2018; Shulman et al , 2018). In these studies, total cfDNA levels were frequently increased in the plasma of sarcoma patients compared with the cancer‐free controls.…”
Section: Epidemiology Of Sarcomamentioning
confidence: 99%
“…Interestingly, the usefulness of cfDNA analysis was demonstrated to identify TKI‐resistant mutations (Yoo et al , 2014). In a series of CHSs, ctDNA levels detected by mutated IDH1 correlated with tumor grade and prognosis (Gutteridge et al , 2017). Patient‐specific somatic alterations in cfDNA were observed in OS (Barris et al , 2018) and were associated with inferior outcomes in EwS and OS patients (Shulman et al , 2018).…”
Section: Epidemiology Of Sarcomamentioning
confidence: 99%
“…A pilot study has shown that detection of IDH1 or IDH2 mutant molecules is associated with high‐grade chondrosarcoma and a worse prognosis …”
Section: Multiple Enchondromas (Aka Enchondromatosis)mentioning
confidence: 99%
“…Further studies found that the overall survival of CS patients with IDH1/IDH2 mutations was significantly lower than that of patients without IDH1/IDH2 mutations [132]. Gutteridge et al identified mutant IDH in the plasma of chondrosarcoma patients [133]. The authors demonstrated that cell-free IDH1/IDH2 could be detected in high-grade chondrosarcoma and dedifferentiated chondrosarcoma patients during the preoperative period; moreover, a high level of mutant IDH correlated with poor prognosis [133].…”
Section: Chondrosarcomamentioning
confidence: 99%
“…The authors demonstrated that cell-free IDH1/IDH2 could be detected in high-grade chondrosarcoma and dedifferentiated chondrosarcoma patients during the preoperative period; moreover, a high level of mutant IDH correlated with poor prognosis [133]. Mutant IDH1 was detected in plasma prior to traditional radiological imaging and clinical changes in patients whose tumors relapsed or metastasized during follow-up periods [133].These results indicate that mutated IDH in circulation may be a potential non-invasive biomarker to monitor chondrosarcoma patients in the clinical setting. Accumulating evidence has demonstrated that the COL2A1 [134] and exostosin glycosyltransferase (EXT1 or EXT2) genes are also frequently altered in CS [134,135].…”
Section: Chondrosarcomamentioning
confidence: 99%